2015 ACC/AHA/SCAI Focused Update on Primary Percutaneous Coronary Intervention for Patients With ST-Elevation Myocardial Infarction: An Update of the 2011 ACCF/AHA/SCAI Guideline for Percutaneous Coronary Intervention and the 2013 ACCF/AHA Guideline for the Management of ST-Elevation Myocardial Infarction - Levine, Glenn N., MD, FACC, FAHA; O’Gara, Patrick T., MD, FACC, FAHA; Bates, Eric R., MD, FACC, FAHA, FSCAI; Blankenship, James C., MD, FACC, FAHA, FSCAI; Kushner, Frederick G., MD, FACC, FAHA, FSCAI; Bailey, Steven R., MD, FACC, FSCAI; Bittl, John A., MD, FACC; Brindis, Ralph G., MD, MPH, MACC, FSCAI, FAHA; Casey, Donald E., MD, MPH, MBA, FAHA; Cercek, Bojan, MD, FACC, FAHA; Chambers, Charles E., MD, FACC, FSCAI; Chung, Mina K., MD, FACC, FAHA; et al. (Journal of the American College of Cardiology, 2016)
Table of Contents Preamble1236 Introduction1237 Methodology and Evidence Review1237 Organization of the GWC1338 Review and Approval1238 Culprit Artery-Only Versus Multivessel PCI1239 Aspiration Thrombectomy1240 References1241 Appendix 1 Author Relationships With Industry and Other Entities (Relevant)1243 Appendix 2 Author Relationships With Industry and Other Entities (Relevant)1245 Appendix 3 Reviewer Relationships With Industry and Other Entities (Relevant)--2015 Focused Update on Primary Percutaneous Coronary Intervention for Patients With ST-Elevation Myocardial Infarction (Combined Peer Reviewers From 2011 PCI and 2013 STEMI Guidelines)1247 Preamble To ensure that guidelines reflect current knowledge, available treatment options, and optimum medical care, existing clinical practice guideline recommendations are modified and new recommendations are added in response to new data, medications or devices. Names are listed in alphabetical order within each category of review.According to the ACC/AHA, a person has a relevant relationship IF: a) the relationship or interest relates to the same or similar subject matter, intellectual property or asset, topic, or issue addressed in the document; or b) the company/entity (with whom the relationship exists) makes a drug, drug class, or device addressed in the document, or makes a competing drug or device addressed in the document; or c) the person or a member of the person's household has a reasonable potential for financial, professional, or other personal gain or loss as a result of the issues/content addressed in the document.ACC indicates American College of Cardiology; AHA, American Heart Association; SCAI, Society for Cardiovascular Angiography and Interventions; STEMI, ST-elevation myocardial infarction; PCI, percutaneous coronary interventions; TIMI, Thrombolysis In Myocardial Infarction; and VA, Veterans Affairs.